1998
DOI: 10.1172/jci2237
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic protein-1 (bone morphogenetic protein-7) reduces severity of injury after ischemic acute renal failure in rat.

Abstract: We have shown that osteogenic protein-1 (OP-1) (bone morphogenetic protein-7) is responsible for the induction of nephrogenic mesenchyme during embryonic kidney development. Gene knock-out studies showed that OP-1 null mutant mice die of renal failure within the first day of postnatal life. In the present study, we evaluated the effect of recombinant human OP-1 for the treatment of acute renal failure after 60 min bilateral renal artery occlusion in rats. Bioavailability studies in normal rats indicate that ‫ف… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
243
1
9

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(259 citation statements)
references
References 33 publications
6
243
1
9
Order By: Relevance
“…emia, infusion of BMP-7 reduces severity of renal injury and suppresses inflammation by downregulation of intercellular adhesive molecules (20). Interstitial inflammation and fibrogenesis associated with unilateral ureteral obstruction (UUO) are also prevented in vivo by administration of BMP-7 at the time of UUO (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…emia, infusion of BMP-7 reduces severity of renal injury and suppresses inflammation by downregulation of intercellular adhesive molecules (20). Interstitial inflammation and fibrogenesis associated with unilateral ureteral obstruction (UUO) are also prevented in vivo by administration of BMP-7 at the time of UUO (21).…”
Section: Discussionmentioning
confidence: 99%
“…Its expression in the kidney has been suggested to be decreased in response to injury (18,19). Furthermore, administration of BMP-7 in models of chronic and acute renal failure results in a reduction of renal interstitial injury (20,21). The second aim of this study was therefore to examine the effect of BMP-7 on HA generation by PTC and to determine how this affects PTC monocyte interactions.…”
mentioning
confidence: 99%
“…Collectively, these studies have confirmed that BMPs have important roles in the development of the skeleton, nervous system, eye, kidney, heart and primordial germ cells (Vukicevic & Sampath, 2004).…”
Section: Developmental Biologymentioning
confidence: 58%
“…BMPs have been successfully tested in clinical trials and subsequently approved for treating skeletal defects (Vukicevic & Sampath, 2004). Their unique ability to transform muscle into bone (Urist, 1965;Yamaguchi et al, 1991) has been used to 'pre-tailor' cranio-facial bones in the back muscles of patients (Fig 3).…”
Section: Tissue Regenerationmentioning
confidence: 99%
“…Expression regulation of both these ligands and receptors follows a certain timing during development; for example, although the peak for type I receptors occurs on embryonal day 18, lowering thereafter [Ikeda et al, 1996], BMP type II receptors are continuously expressed into adult life in rat kidneys [Vukicevic et al, 1998;Bosukonda et al, 2000].…”
Section: Discussionmentioning
confidence: 99%